1993
DOI: 10.1161/01.cir.88.5.2235
|View full text |Cite
|
Sign up to set email alerts
|

Helical and retrograde secondary flow patterns in the aortic arch studied by three-directional magnetic resonance velocity mapping.

Abstract: Helical and retrograde streams are consistent features of intra-aortic flow in healthy subjects that result, at least in part, from the curvature of the arch and the pulsatility of flow in it. They may have significance in relation to circulatory dynamics and the pathogenesis of atheroma in the arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

54
379
1
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(438 citation statements)
references
References 24 publications
54
379
1
4
Order By: Relevance
“…Findings from previous qualitative analyses of flow patterns showed righthanded helical flow patterns in the AAo and left-handed helicity in the DAo (17,19,20,23,38). Our data suggests that this helicity, which is derived from the in-plane component of the flow direction, is reflected by the distribution of WSS circ as shown in Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Findings from previous qualitative analyses of flow patterns showed righthanded helical flow patterns in the AAo and left-handed helicity in the DAo (17,19,20,23,38). Our data suggests that this helicity, which is derived from the in-plane component of the flow direction, is reflected by the distribution of WSS circ as shown in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Due to its intrinsic sensitivity to flow and the possibility to acquire true time-resolved three-dimensional (3D) data, in vivo analyses of blood-flow and derived vessel wall parameters are promising. However, earlier reports on MRbased analysis of aortic hemodynamics were either based on incomplete vascular coverage and separately acquired 2D slices (13)(14)(15)(16)(17), a combination of MR mea-surements with computational fluid dynamics (CFD) (18), or on visual and semiquantitative description of 3D flow patterns (19 -23). Most studies were based on 2D slices or in vitro simulations, were focused on WSS averaged over the entire lumen circumference, and did not provide information on the spatial distribution for different vascular angular segments.…”
mentioning
confidence: 99%
“…Previous studies (10,12,14) have described a normal aortic flow pattern including right-handed helical laminar flow oc-cupying the entire aortic lumen in systole, retrograde flow along the inner wall of the distal ascending aorta occurring from the end systole to early diastole, and vortical flow in the sinuses of Valsalva after peak systole and persisting until diastole. Using time-resolved 3D MR velocity mapping, Markl et al (15) and Kvitting et al (16) reported that the vortices in the coronary sinuses were preserved in patients after aortic valve-sparing surgery.…”
mentioning
confidence: 99%
“…Using MR phase-velocity mapping (PVM) flow through a vessel can be measured accurately (15)(16)(17)(18). PVM has been used to measure the mitral regurgitant volume in an indirect way, by subtracting the aortic outflow mea sured in systole from the mitral inflow measured in di astole (19).…”
mentioning
confidence: 99%